The effect of method and germination paper substrate on viability of Eucalyptus pellita F. Mull seed - Naning Yuniarti; Megawati; Budi Leksono (Jurnal Penelitian Kehutanan Wallacea, 2017)
Improper seed handling of Eucalyptus pellita will reduce seed quality, so as to improve the viability of the seed proper handling techniques are needed. To investigate the seed germination potency as a result of seed handling germination seed tests are needed. The purpose of this study was to examine the effect of germination method and paper substrate on the viability of E. pellita seeds. Seeds used in this study were from seedling seed orchard in South Sumatra, South Kalimantan, and Riau. Seed germination methods used in the laboratory tests were method of top paper and between paper tests, besides that, different papers were used such as: paper substrate namely straw paper, towel paper, filter paper, and newspaper. Factorial experimental design completely randomized was used. The results showed that: (1) the method of germination and paper substrate was significant (2) the best paper substrate and germination method was the method of top paper test with used media of newspaper (germination percentage 204 seedling /0.01 grams).